Peran Disiplin Kerja Memediasi Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan - Suantara, I Komang Agus; Astrama, I Made; Dian Maha Yoga, Gede Agus (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the role of work discipline in mediating the influence of leadership style on employee performance at UD. Bali Jepun Abadi in Gianyar. The population in the study were all UD employees. Bali Jepun Abadi in Gianyar as many as 40 people, with a small population, a saturated sampling technique was used. Data was collected using a questionnaire and analyzed using path analysis. Based on testing, it shows that leadership style has a positive and significant effect on employee performance, leadership style has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance, work discipline can mediate the relationship between leadership style and employee performance at UD. Bali Jepun Abadi in Gianyar. Recommended to UD. Bali Jepun Abadi in making decisions can include employees in providing suggestions or input so that the decisions taken by the leadership are the best decisions for the progress of the company.